2017
DOI: 10.5937/industrija45-12144
|View full text |Cite
|
Sign up to set email alerts
|

Relations of intellectual capital components in hotel companies

Abstract: As an invisible asset within a company, in achieving the impact on business processes, intellectual capital uses its three components -human

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Additionally, human capital is a component of IC with an important effect on the SME hotel financial performance, corroborating the results of previous studies which enhance the importance of human resources for hotel financial performance (Laing et al, 2010;Bontis et al, 2015;Adeola, 2016). In fact, the tourism industry depends strongly on the skills and knowledge of the employees (Ognjanović, 2017). Finally, structural capital is the component of IC with minor effect on SME hotel financial performance.…”
Section: Discussion Of the Empirical Resultssupporting
confidence: 86%
“…Additionally, human capital is a component of IC with an important effect on the SME hotel financial performance, corroborating the results of previous studies which enhance the importance of human resources for hotel financial performance (Laing et al, 2010;Bontis et al, 2015;Adeola, 2016). In fact, the tourism industry depends strongly on the skills and knowledge of the employees (Ognjanović, 2017). Finally, structural capital is the component of IC with minor effect on SME hotel financial performance.…”
Section: Discussion Of the Empirical Resultssupporting
confidence: 86%
“…In tourism sector voluminous researchers (such as Bontis et al , 2015; Gomezelj Omerzel and Smolčić Jurdana, 2016; Khalique and Mansor, 2016; Kim et al , 2012; Ognjanović, 2017; Rudež and Mihalič, 2007; Sardo et al , 2018; Zeglat and Zigan, 2013) have conducted their studies and found that intellectual capital has a positive significant effect on the performance of SMEs operating in tourism sector. They argued that the survival, sustainability, and progression of businesses in the tourism sector are mainly based on the identification, utilization, and capitalization of their intellectual capital/intangible resources.…”
Section: Discussionmentioning
confidence: 99%
“…They argued that the tourism sector is still ignored and there is a need to conduct more studies to examine the intellectual capital in TSMEs. Ognjanović (2017) argued that intellectual capital has a significant role in order to enhance the performance of the hotel industry. Earlier studies except those by Khalique and Mansor (2016) did not use the integrated intellectual capital model to examine the impact of intellectual capital on the organizational performance of SMEs operating in the tourism sector.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The hospitality industry is labor-intensive industry and its performance primarily depends on knowledge and skills of all employees (Ognjanović, 2017). Difference between a successful and unsuccessful company is in knowledge and skills (Dabić et al, 2021).…”
Section: Human Resources In Hospitality Industrymentioning
confidence: 99%